Krisis Keberlanjutan Perkembangan Peserta Didik: Tinjauan Psikologis dalam Praktik Pendidikan - YS, Salsabila; Rahmawati, Uci; Dewi, Nindiastuti Nurfitria; Kim, Daemin; Sania, Khaira; Budiman, Nandang (Universitas Muhammadiyah Metro, 2026)
Transitions across educational levels and the shift into the world of work often become highly demanding phases for students, as they require rapid adjustments in learning strategies, academic identity, and social relationships. When these transitions are not adequately supported, students may experience what this article conceptualizes as a crisis of developmental continuity. The purpose of this article is to critically describe this crisis and to examine the psychological, social, and institutional factors that shape the continuity of student development within educational practice. This study employs a systematic literature review by synthesizing peer-reviewed journal articles retrieved from Scopus, ERIC, and Google Scholar. The selection process applied keywords related to developmental sustainability, educational transitions, and psychological variables (self-awareness, self-efficacy, and self-regulation), followed by PRISMA screening procedures, resulting in 31 articles that were analyzed thematically. The review reveals that crises of developmental continuity commonly arise when students’ self-awareness, self-efficacy, and self-regulation weaken during periods of transition, while support from teachers, peers, families, and educational institutions remains insufficient. Programs that strengthen self-regulation, build supportive relational climates, and offer tiered interventions such as PBIS, self-regulated learning training, and peer mentoring are shown to help maintain developmental continuity. The article concludes that sustaining student development should be regarded as an essential indicator of educational quality and requires deliberate collaboration among educators, counsellors, families, and policymakers to design transitional supports that are humane, adaptive, and sustainable.